Perovskites and related mixed oxides : concepts and applications - Granger, P.; Pârvulescu, V. I.; Kaliaguine, S., 1940-; Prellier, Wilfrid (Wiley-VCH, 2016)
This comprehensive handbook and ready reference details all the main achievements in the field of perovskite-based and related mixed-oxide materials. The authors discuss, in an unbiased manner, the potentials as well as the challenges related to their use, thus offering new perspectives for research and development on both an academic and industrial level. The first volume begins by summarizing the different synthesis routes from molten salts at high temperatures to colloidal crystal template methods, before going on to focus on the physical properties of the resulting materials and their rel.- Resumé vydavatel
Keywords: oxidy; oxides; perovskit; elektronické knihy; sborníky; electronic books; papers of several authors